Efecto gastroprotector y capacidad antioxidante del extracto acuoso de las vainas de Caesalpinia spinosa ‘tara’, en animales de experimentación - Callohuari, Rosalía (2017)
Objective: To determine the protective effect of the aqueous extract of the pods of Caesalpinia spinosa (Molina) Kuntze “tara” in the gastric mucosa of experimental animals. Design: Experimental. Institution: Research Center on Biochemistry and Nutrition, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material: Aqueous extract tara pods (AETP) and 36 albino male rats (217g ± 22 g). Interventions: After a 24-hour fast, the albino rats were divided into 6 groups: GI and GII, NaCl 0.9% to 20 mL/kg; GIII, GIV and GV, AETP at doses of 100, 400 and 800 mg/kg respectively; and GVI, Hidroflat 500 mg/kg. An hour later, gastric injury was caused with 70° ethanol and then gastrectomy was performed. Main outcome measures: Percentage of mucosal protection, using the software ImageJ 1.48v, and the antioxidant activity method 2, 2-diphenyl-1-picrylhydrazyl (DPPH). Results: AETP presented tannins and phenolic compounds in large amounts. High antioxidant activity (IC50 = 1, 1 ± 0.04 μg/mL) was exhibited. The highest percentage of protection was observed at doses of 800 mg/kg (99.7%) and 400 mg/kg (73.1%), p<0, 01, confirmed by histopathological analysis. Conclusions: AETP exhibited antioxidant and protective activity in the experimental model of gastric injury induced by ethanol 70°, in a dose-dependent manner.